Proximate analysis of five selected local fruit peels in Kuala Pilah, Negeri Sembilan / Nor Afiqah Che Alwi - Che Alwi, Nor Afiqah (2018)
Fruit peels are considered as waste products and commonly being thrown to the environment. Even though some of the fruit peels were utilised as fertilizer, the potential benefits of fruit peels might offer in food industry for instance are still unknown. In this study, five local fruit peels sample namely, dragon fruit (Hylocereus polyrhizus), banana (Musa acuminate), honeydew (Cucumis melo), watermelon (Citrullus lanatus) and papaya (Carica papaya) were analysed in term of their proximate composition to obtain the nutritional contents such as carbohydrate, protein, fibre, fat and ash. Proximate analysis is also used to analyse moisture content in these fruit peels. The carbohydrate content ranged from 64.10% to 76.29%. Watermelon stated the highest value with 76.29% and surprisingly it was higher compared to the previous study. Banana, stated the highest fibre and fat content among these fruit peels with 7.97 ± 1.25% and 7.93 ± 0.57 % respectively. Protein content ranged from 0.11 ± 0.05% to 0.67 ± 0.07% where papaya stated the highest value with 0.67 ± 0.07%. The ash content varied from 7.09 ± 0.11% and 16.59 ± 0.25% where dragon fruit recorded the highest value with 16.59 ± 0.25%. Lastly, watermelon recorded the highest moisture content with 7.96 ± 1.06%. The overall findings confirmed that these peels are rich in nutritional content. Thus, these fruit peels can be utilized as food and dietary ingredients after appropriate processing in the future.